Marketing strategies of general insurance companies - Khew, Rebekah Yen Lin (2014)
The insurance industry has grown tremendously over the years and competition among the companies has also intensified. The purpose of this project is to gain an insight into the general insurance industry, to obtain an understanding of the marketing strategies adopted by the companies, and make a comparison between the marketing strategies adopted by both local and foreign general insurance companies.